Penyuluhan pedagogi untuk pendidikan dasar pada abad 21 di sekolah Satu atap - Ndaru Mukti Oktaviani; Arrofa Acesta; Adistra Destria Putri (IKIP SILIWANGI, 2023)
Improving the quality of education in Indonesia faces many challenges in its implementation, starting from increasing learning outcomes, understanding, improving skills and so on. In fact, teachers still use teacher-centered learning. One way to deal with this problem is to apply appropriate pedagogical knowledge. Pedagogy itself is the art of teaching. This of course raises questions about the teacher's ability to innovate learning media in accordance with the demands of the 21st century. Based on the results of interviews with the Head of the Cimulya One Roof School it is known that most teachers still need knowledge about pedagogy that is in line with the 21st century. This condition certainly needs to be addressed to increase teacher professionalism. This is what forms the basis for implementing